Adiabatic CMOS-Based Electrostatic MEMS Actuation for Reduced Dynamic Power and Switching Activity. (8th April 2022) - Muthu, P.; Vasanth Raj, P. T.; Bommi, R. M.; Baskar, M.; Selvaganapathi, S.; Sivaprakasam, P.
Abstract : The basic purpose of MEMS actuation is to miniaturize the actuators and sensors for applications in nanoelectronics. The transistor switching current and power supply noises due to voltage drops across the metal lines can impair circuit timing and performance, posing a continuing problem for high-performance chip designers. This work presents an empirical concept of a reconfigurable charge pump based on FPGA for electrostatic actuation of the Microelectromechanical System (MEMS). The goal of the design is to produce enough on-chip voltages for actuating the MEMS that are continuously adaptive and reconfigurable. In this proposed method, pumping capacitors lying in the range of 1-pF have been deployed to decrease the area of design concerned. The various voltages are programmable digitally and created by dynamically altering the number of phases as well as the clock drive levels. The dynamic model is designed by adjusting the number of stages to produce on-chip voltages including clock drive speeds, assuming a purely capacitive load. The proposed model's power consumption can be lowered in the steady state by lowering its clock frequency and electrostatic MEMS actuators with capacitive load. An average of 0.62 W is dissipated by the circuit when the eight stages are triggered. Consequently, with adiabatic and without adiabatic architecture, 0.0186 mW of minimum power difference is obtained.